EFIKASI DAN KUALITAS HIDUP PASIEN SPASME HEMIFASIAL DENGAN SUNTIKAN TOKSIN BOTULINUM TIPE A - Yanni*, Paulus Anam Ong**, Suryani Gunadharma** (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION HEMIFACIAL SPASM IS CHARACTERIZED BY INVOLUNTARY TONIC OR CLONIC MUSCLE CONTRACTION INNERVATED BY IPSILATERAL FACIAL NERVE IT CAN DISTURB PATIENTS QUALITY OF LIFE BOTULINUM TOXIN TYPE A INJECTION IS SAFE EFFECTIVE AND YIELDS IMPROVEMENT OF PATIENTS QUALITY OF LIFE